Reevaluation of the genus Cyclops Müller, 1776 (Cyclopoida: Cyclopidae) in the Laurentian Great Lakes basin: first report of the Palearctic species Cyclops divergens Lindberg, 1936 from Lake Erie and documentation of Cyclops sibiricus Lindberg, 1949 in the St. Marys River - Connolly, Joseph K.; Marshall, Christopher C.; Hudson, Patrick L.; Watkins, James M.; Scofield, Anne E.; Rudstam, Lars G. (Zootaxa, 2022)
Large cyclopoid copepods of the genus Cyclops Müller, 1776 are seldom collected in the Laurentian Great Lakes, with only Cyclops scutifer Sars, 1863 and Cyclops strenuus Fischer, 1851 reported from the region. Rare reports of the species C. strenuus date back to 1972 within the Great Lakes basin. The first specimens reported as C. strenuus were collected from the St. Marys River, and additional specimens have been collected from western Lake Erie since 2013. We examined all available archived materials of C. strenuus from the Great Lakes and determined that specimens from the two localities belong to two separate species, neither of which refer to C. strenuus. Archived specimens collected from the St. Marys River in 1972 and 1995 were reidentified as Cyclops sibiricus Lindberg, 1949, a Holarctic species known from Siberia, Russian Federation, Alaska, USA, and northern regions of Canada. The occurrences of C. sibiricus from the St. Marys River extend the known distribution of the species southward some 1,688 km in the Nearctic region. Cyclops specimens collected from the western basin of Lake Erie in 2013, 2014, and 2019 were identified as the Palearctic species Cyclops divergens Lindberg, 1936 using both conventional taxonomy and genetic barcoding. C. divergens is known from localities across much of Europe and eastward into Central Asia. The occurrences of the species from western Lake Erie constitute the first detection of C. divergens in the Great Lakes and the Nearctic region. Therefore, we expect C. strenuus does not occur in the Great Lakes basin and is likely restricted to the Palearctic region.